Applications of artificial immune systems to computer security: A survey - Fernandes, Diogo A. B. (2020)
Submitted by FAZENDEIRO (paulof@ubi.pt) on 2020-01-05T11:51:39Z No. of bitstreams: 1 1-s2.0-S221421261630240X-main.pdf: 1148870 bytes, checksum: f32ca93099fce1fff405ec47f55d3105 (MD5)